Perilaku Pedagang Pasar Bandar Kecamatan Mojoroto Kota Kediri Dalam Prespektif Prinsip Dasar Pasar Islami - Dennis Ulfan Nanda; Khusnul Fikriyah (ITB AAS INDONESIA Surakarta, 2020)
Buying and selling activities are one of the community’s needs as facilities and infrastructure of daily needs. Here, the market as one of the tools where there is buying and selling interaction. The marketing environment can change and be uncertain and provide not only opportunities but also threats. The Bandar market is a traditional market that sells the needs for essential materials at an affordable price for the community. The purpose of this research is to determine the behaviour of traders and compliance with the basic principles of Islamic markets. This type of research uses descriptive qualitative research. Data collection techniques using observation, interview, and documentation. The conclusion of this research is the traders’ behaviour in the Bandar market which already tolerable and precise even though the city market is essentially a conventional market, and traders in the Bandar market already apply the principle of Ar-Ridhla, healthy competition, honesty, openness, and justice properly. Keywords : Traditional market, behavior of traders, basic principles of islamic market